Cochlear Implant Complicated by Nontuberculous Mycobacteria Infection: Report and Literature Review - Haidee Chen; Erik B. Vanstrum; Rodell Santuray; Adam Xiao; Akira Ishiyama (Case Reports in Otolaryngology)
Conclusion: NTM is a rare cause of postsurgical infections following cochlear implantation. It is especially important to consider this in cases of indolent, antibiotic-resistant infections to optimize patient treatment.